Evaluation of the Intravesical Ureters after Failed Endoscopic Treatment of Vesicoureteral Reflux with Dextranomer/hyaluronic Acid in Children via Light and Transmission Electron Microscopic Analysis. A Matched Case-Control Study - Izol, Volkan; Kuyucu, Yurdun; Acikalin, Arbil; Deger, Mutlu; Aridogan, Ibrahim Atilla; Polat, Sait; Satar, Nihat (Urology Journal, 2019)
Introduction: The cytokine profile and the ultrastructural changes of refluxing ureterovesical junctions(UVJs) of children treated with failed dextranomer/hyaluronic-acid (Dx/HA) injections were investigated using immunohistochemical methods and transmission electron microscopy(TEM). Patients and Methods: Eighteen children who had undergone injection for reflux were included the study. The smooth muscle arrangement of the ureteral wall, transforming growth factor-? (TGF-?1),vascular-endothelial-growth factor (VEGF) and CD34 were evaluated immunohistochemically, and the results were compared with 10 age-matched autopsy specimens as controls. The ultrastructural evaluation and morphological description was made semi-quantitatively and compared with published data. Result: Four of the patients (22%) were male, and 14 (78%) were female. The mean age of the patients was 105.4 ± 44.5(48-184) months. There was no correlation between the vesicoureteral reflux (VUR) grade and age (P = 0.85). The mean VEGF and CD34 scores were 16.2 ± 9.6 (0-90) cells per HPF and 10.2 ± 3.5 (4-16) vessels per HPF in ureters with reflux; these values were 60.6±16.4 (32-84) cells per HPF and 17.8 ± 4.1 (12-24) vessels per HPF in the control group. The amount of VEGF and CD34 were significantly decreased in patients compared with the control group (P < 0.001, P < 0.001).The TGF-?1 levels were significantly higher in patients with VUR compared with the control group (34.2 ± 19.9 vs 5.0±1.9; P=0.001).The amount of VEGF, CD34, and TGF-?1 were not correlated with the grade of reflux (P = 0.26, P = 0.94, and P = 0.42, respectively). Ultrastructural changes in the muscle cells were observed in all the VUR specimens (Grade II-IV). Conclusion: Refluxing ureters exhibited immune-histopathological abnormalities and ultrastructural changes of the muscle cells in all VUR specimens in the ureterovesical junctions of children treated with failed Dx/HA injections for reflux.